Bee venom therapy: Potential mechanisms and therapeutic applications. (15th June 2018) - Zhang, Shuai; Liu, Yi; Ye, Yang; Wang, Xue-Rui; Lin, Li-Ting; Xiao, Ling-Yong; Zhou, Ping; Shi, Guang-Xia; Liu, Cun-Zhi
Abstract: Bee venom is a very complex mixture of natural products extracted from honey bee which contains various pharmaceutical properties such as peptides, enzymes, biologically active amines and nonpeptide components. The use of bee venom into the specific points is so called bee venom therapy, which is widely used as a complementary and alternative therapy for 3000 years. A growing number of evidence has demonstrated the anti-inflammation, the anti-apoptosis, the anti-fibrosis and the anti-arthrosclerosis effects of bee venom therapy. With these pharmaceutical characteristics, bee venom therapy has also been used as the therapeutic method in treating rheumatoid arthritis, amyotrophic lateral sclerosis, Parkinson's disease, Alzheimer's disease, liver fibrosis, atherosclerosis, pain and others. Although widely used, several cases still reported that bee venom therapy might cause some adverse effects, such as local itching or swelling. In this review, we summarize its potential mechanisms, therapeutic applications, and discuss its existing problems. Highlights: Bee venom therapy has been used for many diseases, especially rheumatoid arthritis, PD, and others in clinical treatment. Bee venom therapy exerts not only pharmacological actions from bee venom but also a mechanical function from stimulation. BVT might cause negative effects such as systemic reactions, skin problems and nonspecific reactions.